2022
DOI: 10.1101/2022.08.01.502338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the contribution of subject and group factors in brain activation

Abstract: Human behavior is known to be idiosyncratic, yet research in neuroscience typically assumes a universal brain-behavior relationship. Here we test this assumption by estimating the level of idiosyncrasy in individual brain-behavior maps obtained using human neuroimaging. We first show that task-based activation maps are both stable within an individual and similar across people. Critically, although behavior-based activation maps are also stable within an individual, they strongly diverge across people. A compu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Various neuropsychiatric diseases have already been associated with increased variability compared to healthy populations, such as ADHD (Kofler et al, 2013; Tamm et al, 2012), Alzheimer’s Disease (Tales et al, 2012; Tse et al, 2010), as well as schizophrenia, depression, and borderline disorder (Kaiser et al, 2008; also see Dinstein et al, 2013). Furthermore, recent work has suggested that neural activity associated with experimental factors is highly consistent across participants, but that neural activity associated with fluctuations in task performance has high inter-subject variability, but is stable within individuals over time (Nakuci et al, 2022). These findings suggest that neural fluctuations relating to performance could in itself be an individual trait, though their reliability over time and contexts remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Various neuropsychiatric diseases have already been associated with increased variability compared to healthy populations, such as ADHD (Kofler et al, 2013; Tamm et al, 2012), Alzheimer’s Disease (Tales et al, 2012; Tse et al, 2010), as well as schizophrenia, depression, and borderline disorder (Kaiser et al, 2008; also see Dinstein et al, 2013). Furthermore, recent work has suggested that neural activity associated with experimental factors is highly consistent across participants, but that neural activity associated with fluctuations in task performance has high inter-subject variability, but is stable within individuals over time (Nakuci et al, 2022). These findings suggest that neural fluctuations relating to performance could in itself be an individual trait, though their reliability over time and contexts remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis utilized a dataset consisting of 50 healthy subjects (25 females; Mean age = 26; Age range = 19-40) that has been described elsewhere 46 . All subjects were screened for any history of neurological disorders or MRI contraindications.…”
Section: Datasetmentioning
confidence: 99%